Complex drivers of primary production along an anthropised estuary (Seine estuary—France) - Serre-Fredj, Léon; Chasselin, Léo; Jolly, Orianne; Claquin, Pascal (Frontiers in Environmental Science, 2023)
The Seine estuary is a typical model of a system in which phosphorus (P) inputs have been considerably reduced to reduce past eutrophication, with a parallel decrease in phytoplankton biomass. However, reducing P alone while concentrations of nitrate (N) remains high led to a dystrophic nutrient balance in the estuary (high N/P and N/Si). To identify the drivers of primary production and phytoplankton communities in the highly anthropised Seine estuary, sampling was performed along a 110-km stretch over a period of three years. Photosynthetic parameters were measured with a single turnover active fluorimeter and the phytoplankton community was assessed using a fluoroprobe and flow cytometry. The results revealed an annual primary production of 33 g C.m-2.y-1 which was largely controlled by light availability (turbidity) but also by nutrients in late spring and summer period. Massive blooms, not seen since 2002, were observed in a specific area of the estuary. None of the nutrients measured explained the particular location of the blooms but phytoplankton production and productivity indicators were higher in this specific zone excluding a biomass accumulation phenomenon. The local effect of tide slowdown increasing water residence time in this exact part of the estuary could explain the bloom area. The question thus arises: does phosphate play a role as a limiting nutrient? The diatom bloom led to total depletion of Si, but no clear limitation of P was observed. Nevertheless, the decrease in Si appears to have played a key role by triggering a succession from diatoms (microphytoplankton) to chlorophytes (nanophytoplankton) and hence affecting phytoplankton composition. The N/P balance appeared to be more important than the absolute concentration of P to explain the phytoplankton dynamics and the biomass decrease observed the last decades.